Complement updates in optic neuritis - He, Yuhong; Guo, Kai; Xin, Jifu (Frontiers in Neurology, 2025)
Optic neuritis (ON) is an inflammatory condition of the optic nerve associated with demyelinating diseases like multiple sclerosis, neuromyelitis optica spectrum disorder, and myelin oligodendrocyte glycoprotein antibody-associated disease. The complement system is crucial in ON pathogenesis, driving blood-optic nerve barrier disruption, inflammation, and tissue damage. This review explores the complement activation pathways—classical, alternative, and lectin—and their roles in ON progression. Key proteins such as C3, C5, and terminal pathway components are highlighted as central to disease mechanisms. Recent advances in complement-targeted therapies, including C1q blockers, C3 and C5 inhibitors, show promising results in clinical and preclinical studies. Novel therapies, like anaphylatoxin receptor blockers and recombinant factor H, expand the treatment landscape, while plasma exchange remains vital for severe, corticosteroid-resistant cases. Challenges remain, such as ON heterogeneity, the long-term safety of complement inhibition, and the need for personalized approaches. Future studies should focus on unraveling complement-mediated mechanisms, identifying biomarkers, and refining therapeutic strategies. This review highlights the critical role of complement in ON and the latest therapeutic advances to improve patient outcomes.